Jung, Individuation, and Moral Relativity in Qohelet 7:16-17 - Kotzé, Zacharias (Journal of religion and health, 2014)
Qohelet's warning in chapter 7:16 not to be too righteous' has commonly been interpreted by biblical scholars in ways that acquit the author of teaching immorality. This article approaches the text from a psychological critical perspective, bringing it into dialogue with the psychological maturation process of individuation in Jungian psychology. The confrontation with the shadow, made up of reprehensible qualities residing in the unconscious that a person wishes to deny, forms the prologue to this process. Projection or repression of these primitive instincts can lead to various problems, such as stagnation and neurosis. Raising the shadowy, primitive, and archaic content of the unconscious to consciousness and integrating it with the ego, however, leads to a mysterious union of opposites and a new personality, a self' that transcends consciousness.